PERTUMBUHAN GEREJA DI MASA PANDEMI - Yusup Rogo Yuono (SAGACITY : Journal of Theology and Christian Education, 2020)
The church instills experiencing growth despite the pandemic. Quantitative growth is difficult to detect, but quality growth is easily observed, among others, through the involvement of the lay congregation in leading house worship due to the prohibition on gathering congregations in the church. Increased concern for others as a form of love; Diaconia is mostly done by the church through philanthropic services. Another church's progress is seen in its ability to become a smart church with a shift from conventional to digitalization. As a conclusion, during this pandemic period, the church has shown its quality as a church, which is present and contributes to the community.